DIGITAL FINANCIAL BEHAVIOR AND THE RISE OF BUY-NOW-PAY-LATER ECONOMIES IN EMERGING MARKETS - Indra Wijaya (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
The development of financial technology has driven a transformation in people's financial behavior, particularly in developing countries experiencing accelerated digitalization. One prominent phenomenon is the increasing use of buy-now-pay-later (BNPL) services, which offer easy access to credit without conventional banking procedures. This study aims to analyze the relationship between digital financial behavior and BNPL-based economic growth in developing markets through a literature review approach. The method used is a literature review, reviewing various scientific sources, including international journals, industry reports, and relevant academic publications. The results indicate that ease of access, low financial literacy, and the influence of a digital lifestyle are the main factors driving BNPL adoption. On the other hand, uncontrolled BNPL use has the potential to increase the risk of consumer debt and individual financial instability. This study also reveals that while BNPL can increase financial inclusion, adaptive regulations and adequate financial education are needed to minimize its negative impacts. Thus, a balance between technological innovation and consumer protection is key to ensuring the sustainability of the digital financial ecosystem in developing countries.